Predicting anxiety and stress among service-learning caregivers the role of person factors - Salaum, Darius N.; Melgar, Ma. Isabel E. (Danyag :the UPV journal of humanities and social sciences, 2010)
"Various researches point to the difficult nature of caregiving work. This study provides a measure of how variables such as hardiness, cognitive appraisals, coping strategies, and certain demographic characteristics predict and explain negative emotion outcomes such as anxiety and stress among service-learning caregivers in Asilo de Molo Iloilo. Results showed that hardiness reduced negative emotions, even when control for conceptual overlap was performed. Threat and stressfulness appraisals exacerbated negative emotions. The use of self blame and avoidance coping as emotion focused forms of coping indicated that caregivers were overwhelmed by the realities in the work environment. Demographic factors, such as age, education, and schedule at work further defined anxiety and stress. These identified variables were important in predicting the negative emotional effects of caregiving institutions for the elderly. The study provides support that personality resource is as significant as the cognitive and behavioral competencies intrinsic within the caregiver."